PENGARUH PENGGUNAAN CRUDE ENZIM PYLORIC CAECA DAN LAMA FERMENTASI TERHADAP MUTU BEKASEM IKAN BILIH (Mystacoleucus padangensis) - Syahrul '; Dewita '; Ayu Diana (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
The objective of this research was to find out the influence of enzymepyloric caeca and fementation duration to quality bekasem bilih fish. Qualityparameters measured were using preferred test, pH, acid number, protein, water,and NPN. Results of the research hopely could be used as a business an alternativefor farmers to produce bekasem bilih fish. Bekasem fermentation product is afresh water fish that taste sour.Research method used was the method of experimental design, wasComplete Random Design (RAL), with two factors, namely the three levels Afactors without pyloric caeca enzim, pyloric caeca 25% (E25), and the addition ofenzyme pyloric caeca concentration of 50% (E50). B factors three levelsfermentation duration: 5 (T5), 10 (T25), and 15days (T15).Results of research on the level of consumer acceptance bekasem bilih fish(Mystacoleucus padangensis) treatment with the addition of enzyme extractpyloric caeca generally preferred by consumers. During the fermentation pH valueand protein tend to decline, as well as water content, NPN, and acid number.Instead tend to decline protein content tend to increase during fermentation. pHvalues ranging from 4.0 to 5.0, the water concentration 32.20% - 33.85% , NPN16%- 1.29%, and acid number 36.99% - 55.22%.